Optical image transmission through an optical fiber by spectral coding - Bobrinev, V.I.; Jeon, H.-W.; Son, J.-Y. (Proceedings of SPIE - The International Society for Optical Engineering, 1996)
One way parallel image transmission through the multi-mode optical fiber was realized by the spectral coding method. Multistripe holographic gratings were used for direct transmission of 10 x 20 pixel two dimensional images. It was done by decomposing light from point source in a two dimensional spectrum, each wavelength corresponding to one image pixel. Copyright ？ 1996. The Society of Photo-Optical Instrumentation Engineers.